An updated age for the Xujiayao hominin from the Nihewan Basin, North China: Implications for Middle Pleistocene human evolution in East Asia. Issue 106 (May 2017) - Ao, Hong; Liu, Chun-Ru; Roberts, Andrew P.; Zhang, Peng; Xu, Xinwen
Abstract: The Xujiayao site in the Nihewan Basin (North China) is one of the most important Paleolithic sites in East Asia. Twenty Homo fossils, which were previously assigned to an archaic Homo sapiens group, have been excavated along with more than 30, 000 lithic artifacts and ∼5000 mammalian fossil specimens. Dating of the Xujiayao hominin has been pursued since its excavation in the 1970s, but its age has remained controversial because of limitations of the dating techniques that have been applied to available materials. Here, we report new ages for the Xujiayao hominin based on combined electron spin resonance (ESR) dating of quartz in the sediments and high-resolution magnetostratigraphy of the fluvio-lacustrine sequence. The magnetostratigraphy suggests that the upper Matuyama and Brunhes polarity chrons are recorded at Xujiayao. The ESR dating results indicate a pooled average age of 260–370 ka for the Homo -bearing layer, which is consistent with its position within the middle Brunhes normal polarity chron indicated by magnetostratigraphy. This age estimate makes the Xujiayao hominin among the oldest mid-Pleistocene hominins with derived Neanderthal traits in East Asia. This age is consistent with the time when early Denisovans, a sister group of Neanderthals, appeared and colonized eastern Eurasia. Our updated age and the Neanderthal-like traits of the Xujiayao Homo fossils, particularly the Denisovan-like molar teeth, make it possible that the Xujiayao hominin could represent an early Denisovan.